Skin and Mucocutaneous Manifestations: Useful Clinical Predictors of HIV/AIDS - Chopra, Shashi (JCDR Research and Publications (P) Limited, 2012)
BACKGROUND AND AIMS: The HIV infection is associated with several dermatological conditions which may be the first pointer towards the existence of HIV. These may present with unusual and atypical manifestations in the course of the HIV infection. Keeping this in mind, the seroprevalence of HIV in these persons and the spectrum of the skin and the mucocutaneous lesions in the HIV positive patients was studied. METHODS: The current prospective study was conducted over a period of 3 years (2006-2008). A total of 604 persons who had any kind of skin and mucocutaneous infections were screened for the HIV infection as per the NACO guidelines after recording their clinical and epidemiological profiles. RESULTS: Out of the 604 patients who were screened, 90(14.90%) were seropositive for the HIV-I antibodies and none was positive for the HIV-2 antibodies. Seventy three point thirty three percent 73.33 of the seropositive patients were in the age group of 15-40 years, with a male-female ratio of 1:1.05. The heterosexual route was the most common mode of transmission (86.6%).A wide range of infectious and noninfectious lesions were observed. In the HIV seropositive patients, oral candidiasis (32.22%) was the most common infectious disease which was observed, followed by herpes zoster (13.33%), genital warts (7.77%) and genital herpes (6.66%). The most common noninfectious manifestation was seborrhoic dermatitis (8.88%), followed by pruritic papular eruptions (7.77%). CONCLUSION: As there is a high prevalence of the HIV infection in patients who have skin and mucocutaneous disorders, the doctors, during the investigation of these patients, must have a high level of suspicion for the HIV infection in their mind. An early detection of HIV optimizes the chemoprophylaxis for many opportunistic mucocutaneous disorders.